PENGARUH KOMPENSASI TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN NIAS BARAT - Hermanto Hia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
This research aims to determine the effect of compensation on employee morale at the West Nias Regency Transportation Service. The type of research used in this research is quantitative research with a causal nature. The population and sample used in this research were all employees at the West Nias Regency Transportation Service totaling 61 employees. The analytical method that will be used to test the hypothesis used in this research is simple linear regression analysis. The results of this research show that compensation has a positive and significant effect on employee morale at the West Nias Regency Transportation Service Office. Based on the research results that have been described, it can be concluded that compensation has an effect on employee morale at the West Nias Regency Transportation Service Office. The suggestions in this research are, 1) so that employees produce good and appropriate work results, the organization pays attention to the compensation given to employees, such as compensation must be in accordance with their work results. 2) To complete work on time, employees must comply with work regulations that have been established such as work entry times and work leave times. 3) In solving problems, it is hoped that employees will not give up in solving work problems assigned to them. 3) To complete work well, effectively and efficiently, employees should work together to complete each job.